2000
DOI: 10.1177/0013161x00361004
|View full text |Cite
|
Sign up to set email alerts
|

Unsettled Moments in Settled Discourse: Women Superintendents’ Experiences of Inequality

Abstract: In this article, the discourse of 12 women superintendents is examined with the expressed aim of determining if patterns in their talk about their superintendency experiences contain events or episodes of inequality. The study's examination is guided by an adaptation of Swindler's theory of "settled" and "unsettled" social periods. Qualitative inquiry and analysis methods are used to identify emerging themes or topics of talk. Five topics of talk emerge from the narrative data: power, silence, style, responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 27 publications
2
50
0
Order By: Relevance
“…A little more than 20 years ago, a handful of researchers, primarily women, began to focus on women in administration (see, e.g., Adler, Laney, & Packer, 1993;Dunlap & Schmuck, 1995;Ortiz, 1982;Schmuck, 1975;Shakeshaft, 1989) and even later to study women in the superintendency (Bell, 1995;Brunner, 1999aBrunner, , 1999bBrunner, , 2000aBrunner, , 2000bChase, 1995;Chase & Bell, 1990;Grogan, 1996;Kamler & Shakeshaft, 1999;Maienza, 1986;Marietti & Stout, 1994;Pavan, 1999;Sherman & Repa, 1994;Skrla, Reyes, & Scheurich, 2000;Tallerico, 2000aTallerico, , 2000bTallerico & Burstyn, 1996;. In addition, a few historians carefully chronicled the phenomenon of women in the superintendency (see Blount, 1998;Hansot & Tyack, 1981;Tyack & Hansot, 1982).…”
Section: Women Superintendents: Literature In Briefmentioning
confidence: 99%
“…A little more than 20 years ago, a handful of researchers, primarily women, began to focus on women in administration (see, e.g., Adler, Laney, & Packer, 1993;Dunlap & Schmuck, 1995;Ortiz, 1982;Schmuck, 1975;Shakeshaft, 1989) and even later to study women in the superintendency (Bell, 1995;Brunner, 1999aBrunner, , 1999bBrunner, , 2000aBrunner, , 2000bChase, 1995;Chase & Bell, 1990;Grogan, 1996;Kamler & Shakeshaft, 1999;Maienza, 1986;Marietti & Stout, 1994;Pavan, 1999;Sherman & Repa, 1994;Skrla, Reyes, & Scheurich, 2000;Tallerico, 2000aTallerico, , 2000bTallerico & Burstyn, 1996;. In addition, a few historians carefully chronicled the phenomenon of women in the superintendency (see Blount, 1998;Hansot & Tyack, 1981;Tyack & Hansot, 1982).…”
Section: Women Superintendents: Literature In Briefmentioning
confidence: 99%
“…Research studies relate this situation to the challenges associated with these positions. These challenges exist at all levels, from entry level (Kalbus, 2000;Derrington and Sharratt, 2009;Miller, Washington, and Fiene, 2006;Montz and Wanat, 2008;Shamsodin, Saeed, and Shahla, 2012) to workplace level (Brunner, 2000;Gewertz, 2006;Grogan's, 2008;Palladino, Haar, Grady, and Perry, 2007;Hanan, 2011;Quilantan and Menchaca-Ochoa, 2004).…”
Section: Background Of the Problemmentioning
confidence: 99%
“…In another qualitative study that explored what it is like to be a female superintendent, Grogan (2000) composed a poem from the interview data of a participant who lamented many aspects of her job, including discrimination. Brunner (2000) also carried out a qualitative study examining the same subject matter in which he conducted interviews with 12 women superintendents to find out if there were issues of inequality in their experiences. Brunner's study confirmed the pervasive and persistent existence of gender bias in the workplace.…”
Section: Gender Bias and Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…While females selected this indicator as one of their top choices, this is consistent with findings from a 2003 AASA national survey (Grogan & Brunner, 2005) that indicated that women bring the strengths of interpersonal skills and the ability to maintain organizational relationships to their position. Research indicates that women are much more collaborative, establishing power with others, while men are more authoritarian, employing power over others (Brunner, 2000). Women focus on creating a positive group effort while men focus on demonstrating their leadership (Banks, 1995).…”
Section: Univariate Descriptive Statisticsmentioning
confidence: 99%